Designing Key Performance Indicators (KPIs) for Evaluating Sales Performance and Distribution Systems in the Fast-Moving Consumer Goods (FMCG) Sector Using the Balanced Scorecard and Analytical Hierarchy Process (AHP) Methods at PT X - Muhammad Fadril Sonaska; Hery Irwan (Greenation International Journal of Engineering Science, 2026)
The Fast-Moving Consumer Goods (FMCG) industry requires companies to maintain high operational efficiency, effective sales performance, and reliable distribution systems to sustain competitiveness in an increasingly dynamic market. PT X currently evaluates sales performance primarily based on sales achievement, while other strategic aspects, including customer satisfaction, distribution effectiveness, internal business processes, and employee capability development, have not been comprehensively measured. This condition limits management's ability to evaluate organizational performance holistically and identify strategic improvement priorities. Therefore, this study aims to design Key Performance Indicators (KPIs) for evaluating sales and distribution performance using the Balanced Scorecard (BSC) method and determine KPI priorities through the Analytical Hierarchy Process (AHP). This research employed a quantitative descriptive approach involving interviews, observations, company document analysis, and expert judgment from sales managers, distribution managers, and logistics supervisors. The Balanced Scorecard was utilized to formulate strategic objectives and performance indicators based on four perspectives: financial, customer, internal business processes, and learning and growth. Furthermore, AHP was applied to determine the priority weights of each perspective and KPI through pairwise comparison matrices. The study identified twenty-four KPIs distributed across the four Balanced Scorecard perspectives. The AHP results indicated that the Financial Perspective received the highest priority weight (0.39), followed by Customer (0.28), Internal Business Process (0.20), and Learning and Growth (0.13). The highest-priority KPIs include Sales Achievement, On-Time Delivery, Fill Rate, Customer Retention Rate, and Distribution Cost Ratio. The proposed KPI system provides a comprehensive framework for evaluating organizational performance and supporting strategic decision-making to improve sales effectiveness and distribution efficiency in PT X.